Analysis of performance in orienteering with treadmill tests and physiological field tests using a differential global positioning system - Larsson, P.; Burlin, L.; Jakobsson, E.; Henriksson-Larsen, K. (Journal of Sports Sciences, 2002)
The aim of this study was to determine the physiological responses to orienteering by examining the interrelationships between the information provided by a differential global positioning system (dGPS) about an orienteer's route, speed and orienteering mistakes, portable metabolic gas analyser data during orienteering and data from incremental treadmill tests. Ten male orienteers completed a treadmill threshold test and a field test; the latter was performed on a 4.3 km course on mixed terrain with nine checkpoints. The anaerobic threshold, threshold of decompensated metabolic acidosis, respiratory exchange ratio, onset of blood lactate accumulation and peak oxygen uptake (VO2peak) were determined from the treadmill test. Time to complete the course, total distance covered, mean speed, distance and timing of orienteering mistakes, mean oxygen uptake, mean relative heart rate, mean respiratory exchange ratio and mean running economy were computed from the dGPS data and metabolic gas analyser data. Correlation analyses showed a relationship between a high anaerobic threshold and few orienteering mistakes (r = - 0.64, P < 0.05). A high threshold of decompensated metabolic acidosis and VO2peak were related to a fast overall time (r = -0.70 to -0.72, P < 0.05) and high running speed (r = 0.64 to 0.79, P < 0.05 and P < 0.01, respectively), and were thus the best predictors of performance.